Evidence of Facilitated Electron Transfer on Hydrogenated Self‐Doped TiO2 Nanocrystals. Issue 8 (11th March 2014) - Minguzzi, Alessandro; Sánchez‐Sánchez, Carlos M.; Gallo, Alessandro; Montiel, Vicente; Rondinini, Sandra
Abstract TiO2 nanocrystals are widely used as semiconductor photocatalysts, despite their limited sunlight absorption. The hydrogenation of TiO2 has recently been proposed as a promising new method for enhancing its solar‐driven photocatalytic activity. But, the ability of this hydrogenated TiO2 to transfer electrons across the interface has not been studied in detail. For this reason, the electrochemical properties of hydrogenated self‐doped TiO2−x nanocrystals are studied and compared to commercial anatase TiO2 nanocrystals. Here we use cyclic voltammetry (CV) and scanning electrochemical microscopy (SECM) as tools to characterize the semiconductors and, in particular, to evaluate their reactivity towards redox species in solution. CV is used to evaluate the doping level; we propose the co‐presence of permanent defects, induced by the hydrogenation reductive treatment, as well as temporary ones, induced electrochemically. By using ferrocenemethanol as the redox‐active species, SECM, in a substrate/tip configuration, demonstrates that the electron transfer is facilitated on hydrogenated self‐doped TiO2−x by a potential‐shift of approximately 0.3–0.4 V.